Komunitas Lokal Perspektif HAM dan Hukum Nasional - Thontowi, Jawahir (Unisia, 2016)
There is no a specific term relating to the nation of a local community in Intemational Law. In term of practical meaning, however, the word of indigineous people in international convention obviously indicates to the existing of Indonesian societies, such as Badui, Dayak, Asmat, and Kubu. Inspite of the fact, that the local communities are not identical with legal concept of indigineous people in intemational convention, the 1945 constitution and the anuthonomy of iocal govemment Act No. 32/2005, recognize the term of traditional socities or local customary rules. These are relevant element of indigineous people, but they cannot directly be addressed to name local community. This is not because all local communities in Indonesia are applied modem type of governments, but also because traditional values partly operate in certain local commuriities. In order awamess of law and human rights, it is relevant to take into account local communities and its interest to accommodate into local law enacted by the local perliement.